2017
DOI: 10.1121/1.4979167
|View full text |Cite
|
Sign up to set email alerts
|

Streaming and sound localization with a preceding distractor

Abstract: Localization of a 2-ms click target was previously shown to be influenced by a preceding identical distractor for inter-click-intervals up to 400 ms [Kopčo, Best, and Shinn-Cunningham (2007). J. Acoust. Soc. Am. 121, 420–432]. Here, two experiments examined whether perceptual organization plays a role in this effect. In the experiments, the distractor was designed either to be grouped with the target (a single-click distractor) or to be processed in a separate stream (an 8-click train). The two distractors aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 10 publications
2
21
2
Order By: Relevance
“…Thus, while the similarity of the distractor and target was expected to result in grouping of these two objects into one stream for the one-click distractor, the temporal mismatch in the eight-click distractor was expected to result in the target being processed in a separate stream, possibly reducing any bias due to the immediately preceding one-click distractor. However, as shown in Kopčo et al (2017), in which very similar distractor conditions were tested, the eight-click distractor can actually cause an increase in the response bias.…”
Section: Effect Of Preceding Distractormentioning
confidence: 87%
See 3 more Smart Citations
“…Thus, while the similarity of the distractor and target was expected to result in grouping of these two objects into one stream for the one-click distractor, the temporal mismatch in the eight-click distractor was expected to result in the target being processed in a separate stream, possibly reducing any bias due to the immediately preceding one-click distractor. However, as shown in Kopčo et al (2017), in which very similar distractor conditions were tested, the eight-click distractor can actually cause an increase in the response bias.…”
Section: Effect Of Preceding Distractormentioning
confidence: 87%
“…Two experiments were performed using setup, stimuli, and procedures similar to the previous CP studies (Kopčo et al, 2007;Kopčo et al, 2015;Kopčo et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with our normal-hearing data, which means that broadband sound localization is more immune to both the negative (normal hearing) and positive (plugged hearing) effects of background noise. Although we investigated what happens when targets and background noise overlap in time, auditory spatial processing can adapt to sounds that precede a target sound but do not overlap (Dahmen et al, 2010; Maier et al, 2012; Stange et al, 2013; Phillips, 2014; Kopco et al, 2017; Tolnai et al, 2017; Ferger et al, 2018). However, previous work has shown that adaptation cannot fully explain the effects of concurrent background noise on sound localization (Best et al, 2005), which points toward additional mechanisms.…”
Section: Discussionmentioning
confidence: 99%